A Correlation Study Between Indoor Environmental Quality And Work Productivity In Malaysia - Ho, Hong Yeu (2022)
Indoor environmental quality (IEQ) is a major factor contributing to the health, comfort, and well-being of building occupants. IEQ are broadly divided into four categories including: thermal comfort, indoor air quality (IAQ), visual comfort, and thermal comfort. Meanwhile, work productivity is the primary indicator of an organization’s performance. Business owners strive to acquire productive workers for maximum profit generation. Existing studies found that there was correlation between IEQ satisfaction and work productivity (Mujan, et al., 2019; Ganesh, et al., 2021). Therefore, this study aims to further explore the correlation between IEQ and work productivity in office buildings in Klang Valley, Malaysia. Questionnaire surveys were distributed to office occupants in January 2022. Next, statistical analyses were performed using IBM SPSS Statistics 26 to process raw data into useful statistics. Descriptive statistics showed that office occupants in Klang were generally satisfied with the IEQ conditions in their workplace. Besides, they were known to have high work productivity. Spearman’s correlation test was also conducted to investigate the correlation between IEQ and work productivity. Spearman’s results showed that the IEQ parameters had strong and positive correlation with work productivity. Acoustic comfort had the strongest correlation with work productivity followed by visual comfort, IAQ, and thermal comfort. With these findings, the author wishes to create awareness to building designers, policy makers, and business owners regarding the importance of IEQ on work productivity, and therefore, to contribute effort in improving office IEQ.